THE ROLE OF MADRASAH CULTURE IN FORMATION SELF-CONCEPT OF RELIGIOUS STUDENTS - Subiyantoro Subiyantoro (Universitas Ahmad Dahlan, 2015)
This study aims to: (1) Determine how the socio-cultural-educational Madrasah Aliyah, in city sub-district, city districts, and the Municipality of Yogyakarta. (2) Determine how buildsthe self-concept of students in the process of religious education in Madrasah Aliyah in the Sub-District city, districts city, and in the Municipality of Yogyakarta. (3) Determine how the important of culture Madrasah, in buildsthe self-concept religious Madrasah Aliyah students in the Sub-districts city, districts city, and in the Municipality of Yogyakarta.The results shows that (1) Images of the madrasah culture